2005
DOI: 10.1111/j.1365-2125.2004.02199.x
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol: a haemorrhagic risk factor in patients on warfarin

Abstract: AimTo quantify the effect of paracetamol on the anticoagulant effect of war farin under normal clinical conditions. Patients and methodsIn a prospective double-blind, cross-over, placebo-controlled study, 11 patients on stable warfarin therapy received in random order two 14-day regimens of paracetamol 4 g day − 1 or placebo, with a 14-day or more wash-out period in between, time necessary to fulfil the inclusion criteria. ResultsIn patients on paracetamol, the mean maximum increase in the International Normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 17 publications
1
27
0
6
Order By: Relevance
“…The combination of paracetamol and oral anticoagulant agents is not as safe as generally believed, however, and could induce profound hypocoagulation. Recently, Mahe and colleagues [13 ] have shown that paracetamol 4 g per day for 14 days induced a significant increase in international normalized ratio (INR) in patients receiving a stable treatment of warfarin, increasing the risk of bleeding associated with warfarin. Paracetamol can indeed interact with warfarin and other anticoagulants and can increase prothrombin time.…”
Section: Adequate Dosage For Postoperative Pain Treatmentmentioning
confidence: 99%
“…The combination of paracetamol and oral anticoagulant agents is not as safe as generally believed, however, and could induce profound hypocoagulation. Recently, Mahe and colleagues [13 ] have shown that paracetamol 4 g per day for 14 days induced a significant increase in international normalized ratio (INR) in patients receiving a stable treatment of warfarin, increasing the risk of bleeding associated with warfarin. Paracetamol can indeed interact with warfarin and other anticoagulants and can increase prothrombin time.…”
Section: Adequate Dosage For Postoperative Pain Treatmentmentioning
confidence: 99%
“…In several studies, the concomitant use has been reported to result in an increase in INR [15][16][17][18][19]. Contrary to these results, no paracetamol-related increase in INR values was observed in studies on healthy volunteers [20,21].…”
Section: Introductionmentioning
confidence: 85%
“…Patients with chronic liver disease and history of drug abuse were excluded from the study. In patients on anticoagulation therapy, the international normalized ratio (INR) was closely monitored due to the paracetamol eff ect on increasing the INR 40 . Although there are side eff ects reported with the use of paracetamol, none was recorded in our study.…”
Section: Fig 1 Diff Erences In Pain Perception Between Study Groupsmentioning
confidence: 99%